Pendidikan Seksualitas dalam Lontar Rsi Sembina: Kajian Etnopedagogi: Sexuality Education in the Lontar Rsi Sembina: An Ethnopedagogical Study - I Putu Gede Sutrisna; Asthadi Mahendra Bhandesa (ITScience (Information Technology and Science), 2024)
The results of this study can attract public interest in reading and studying lontar texts as a wealth of literature owned by the Balinese people. By increasing the interest of the Balinese people in reading and studying lontar, there will be a natural retention of vocabulary. The objectives of this study are (1) To determine the structure of the Rsi Sembina lontar text and (2) To determine sexuality education in the Rsi Sembina lontar text. This researcher uses a qualitative descriptive design. The data collection method used in this study is content analysis through document studies in Lontar. The data obtained are reduced or selected according to the research objectives. The data analysis technique in this study includes three activities, namely 1) data reduction, 2) data presentation, and 3) conclusion. The structure of the Rsi Sembina Lontar text includes formal structure and narrative structure. The formal structure in Lontar Rsi Sembina includes the Mangala section (benefits of classical sexuality teachings), corpus (summary of the entire contents of the lontar text), epilogue (general commentary on the text), and language aspects (consisting of Kawi and Hybrid Sanskrit). The Lontar Rsi Sembina text's narrative structure includes the text's theme (teachings of Sexuality or Kama Tattwa) and the speech aspect. The sexuality teachings in Lontar Rsi Sembina include Harmony Teachings (harmony within the scope of Tri Hita Karana), Yoga Sanggama Teachings (Yoga Sanggama and Prayer), Spiritual Healing Teachings (spiritual-informed mantra strokes), Usada Teachings (use of traditional herbs or medicines). There are formal structures and narrative structures in Lontar Rsi Sembina. There are four sexual teachings in Lontar Rsi Sembina.